2011
DOI: 10.1177/194008291100400403
|View full text |Cite
|
Sign up to set email alerts
|

Demography of the Clonal PalmPrestoea Acuminatain the Colombian Andes: Sustainable Household Extraction of Palm Hearts

Abstract: Prestoea acuminata is a highland clonal palm traditionally used as a source of palm hearts by the Awá Indians of Colombia and Ecuador; its commercial use thrived in the 1980´s. Extraction pressure on the resource is particularly strong during Holy Week, as campesinos use it as a substitute for meat. We studied P. acuminata demography at La Planada Reserve, southwestern Colombia, and elaborated a ramet-based matrix model to assess the impact of different palm heart harvest regimes. The 1.5 ha study area had 118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…Some studies have found such habitats provide advantage for palms by increasing survivorship and reducing herbivory (Berry, Gorchov, Endress, & Stevens, 2008), and this may be the case for T. spectabilis . Many palm species are utilized by humans for a variety of purposes, such as the consumption of the palm heart and harvesting of palm leaves for thatch and a variety of other purposes (Gamba‐Trimiño et al, 2011; Gruca et al, 2016; Jansen et al, 2018; Martínez‐Ballesté et al, 2005; Navarro et al, 2011; Reis et al, 2000). Previous studies of palm demography have demonstrated that loss of palm leaves can reduce palm survival, growth and reproduction (Mandle & Ticktin, 2012; Martínez‐Ramos et al, 2010; Ratsirarson et al, 1996;).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies have found such habitats provide advantage for palms by increasing survivorship and reducing herbivory (Berry, Gorchov, Endress, & Stevens, 2008), and this may be the case for T. spectabilis . Many palm species are utilized by humans for a variety of purposes, such as the consumption of the palm heart and harvesting of palm leaves for thatch and a variety of other purposes (Gamba‐Trimiño et al, 2011; Gruca et al, 2016; Jansen et al, 2018; Martínez‐Ballesté et al, 2005; Navarro et al, 2011; Reis et al, 2000). Previous studies of palm demography have demonstrated that loss of palm leaves can reduce palm survival, growth and reproduction (Mandle & Ticktin, 2012; Martínez‐Ramos et al, 2010; Ratsirarson et al, 1996;).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of heart of palm has been documented as a widespread practice in Madagascar that potentially impacts on Critically Endangered palm species (Gruca et al, 2016; Shapcott et al, 2012). Given the long generation time of T. spectabilis , the critically small population sizes and the hapaxanthic reproductive lifecycle, this species is particularly vulnerable to impacts of heart of palm consumption as it kills the plants before they can reproduce (Gamba‐Trimiño et al, 2011; Shapcott et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations